Chemical composition and properties of essential oil of Ferula foetida (Bunge) Regel growing on Mangyshlak peninsula - Sagyndykova, M.S.; Imanbayeva, A.A.; Suleimen, Ye.M.; Ishmuratova, M.Yu. (KSU publ., 2019)
The medicinal plant, Ferula foetida, has been studied, which has a wide range of pharmacological properties. Since ancient times, ferules have been used in folk medicine in various countries (Central Asia, Iran, China, India) for treatment of scabies, wounds, tumors, syphilis, tuberculosis, seizures, hysteria, the gastrointestinal tract, and as an antiparasitic remedy. Chemical composition of Ferula foetida essential oil has been analyzed. The samples were taken from two different populations on Mangyshlak peninsula — on loamy and sandy massifs. Use of GC-MS analyses helped identifying 47 compounds comprising 91.5 % of the total components in the oil. Components of essential oil of two populations — Tuyesu sands and Tynymbay Shoky hills — differ through growing phase. 2,5-Diethylthiophene, 3,4-diethylthiophene, bulnesol, guaiol, myristicine, α-pinene, caryophyllene oxide, 2,5-dipropylthiophene, elemicine, 1-heptatriacontanol, β-transcaryophyllene, β-cis-caryophyllene, α-caryophyllene, β-pinene, dimethyl trisulfide, α-eudesmol, β-eudesmol; β-eudesmene, 2-methylthieno[3.2-b]thiophene, 5,5-dimethyl-4-[(1E)-3-methyl-1,3-butadienyl]-1-oxaspiro[ 2.5]octane, S-(9-thiabicyclo[3.3.1]non-6-en-2-yl are common for both populations. These components have acaricide, antitussive, expectorate effect, as well as anxiolytic, antidepressant, antioxidant, growth stimulating properties. Concentration of major components is higher in plants growing in harsher edaphic conditions. Comparative analysis of essential oil of Ferula foetida growing in Iran, Turkey and Kazakhstan shows differences in the composition. The differences are caused by the climatic conditions. The results of the studies may further be used for standardization of the raw materials.
Keywords: essential oil; Ferula foetida; herbs; Mangyshlak; GC-MS; climate; arid zone; latex